Draft Genome Sequence of Coprobacter fastidiosus NSB1(T) - Chaplin, A. V. (American Society for Microbiology, 2014)
Coprobacter fastidiosus is a Gram-negative obligate anaerobic bacterium belonging to the phylum Bacteroidetes. In this work, we report the draft genome sequence of C. fastidiosus strain NSB1(T) isolated from human infant feces.